(Re)Introducing a Closed Book Exam in Law - Cathy S Sherry; Leon Terrill; Julian Laurens (Legal Education Review)
In the past half century there has been a move towards open book examinations in many tertiary institutions. However, the body of research on open book and more traditional closed book exams is diverse and even contradictory in its findings. Law-specific research is almost non-existent. This article discusses the findings of an empirical research project on the introduction of a closed book exam in the compulsory subject Land Law, in an institution that has only used open book exams. The closed book exam and subsequent research were motivated by concerns about the way in which contemporary students do open book exams, particularly after the invention of the internet. The study found that academic concerns about open book exams had some validity, particularly in relation to heavy reliance on notes, including other students’ notes during the exam. The authors conclude that there are advantages and disadvantages to both open and closed book exams, and that both have a role to play in a balanced assessment strategy.